2009
DOI: 10.1007/s11336-009-9126-z
|View full text |Cite
|
Sign up to set email alerts
|

Clustering Qualitative Data Based on Binary Equivalence Relations: Neighborhood Search Heuristics for the Clique Partitioning Problem

Abstract: equivalence relation, clique partitioning, clustering, heuristics, tabu search, simulated annealing, neighborhood search,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 40 publications
1
45
0
Order By: Relevance
“…Tabu-search results from previous applications, as well as some experimentation, were used to guide our selection of the ψ 0 and η 0 parameters. De Amorim et al (1992) used modest parameter settings of ψ 0 = 5 and η 0 = N/2 in their tabu-search application for clique partitioning; however, Brusco and Köhn (2009) found that more aggressive parameter settings of ψ 0 = N/2 and η 0 = 6N yielded substantially better performance for larger, more difficult problems. Our parameter experiments yielded similar findings for two-mode blockmodeling.…”
Section: Implementation Of the Tabu Search Algorithmmentioning
confidence: 99%
See 3 more Smart Citations
“…Tabu-search results from previous applications, as well as some experimentation, were used to guide our selection of the ψ 0 and η 0 parameters. De Amorim et al (1992) used modest parameter settings of ψ 0 = 5 and η 0 = N/2 in their tabu-search application for clique partitioning; however, Brusco and Köhn (2009) found that more aggressive parameter settings of ψ 0 = N/2 and η 0 = 6N yielded substantially better performance for larger, more difficult problems. Our parameter experiments yielded similar findings for two-mode blockmodeling.…”
Section: Implementation Of the Tabu Search Algorithmmentioning
confidence: 99%
“…For all test problems, the matrix elements were independently generated based on a uniform distribution with equal probability for a value of 0 or 1. The random generation of matrix elements has also been used in other clustering contexts because of its ability to produce difficult test problems that can differentiate the performance of competitive methods (Charon & Hudry, 2006;Brusco & Köhn, 2009). …”
Section: Experimental Test Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our paper further explores this possibility by developing and testing an adaptation of the variable neighborhood search (VNS; algorithm for deterministic two-mode blockmodeling. In part, this exploration is motivated by the fact that there is compelling evidence that VNS often outperforms TS in a number of contexts that require the clustering of objects, including the p-median problem , minimum sum of squares partitioning (Brusco & Steinley, 2007), and clique partitioning (Brusco & Köhn, 2009).…”
Section: Introductionmentioning
confidence: 99%